1996
DOI: 10.1097/00007890-199603270-00017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Allograft Vasculopathy

Abstract: We have previously reported that cell-mediated immunity to vascular endothelium is associated with the development of cardiac allograft vasculopathy (CAV). The mechanism by which a cell-mediated immune response to the coronary vascular is translated into the development of CAV is, however unknown. Peripheral blood mononuclear cells (PBMCs) obtained serially following cardiac transplantation were cocultured with donor-specific human aortic endothelial cells (HAECs) in 47 allograft recipients, 9 of whom had CAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Expression of proliferating cell nuclear antigen (PCNA) is elevated in grafts with TV (10, 11). Further, increased expression of mitogenic factors, such as PDGF, TGFalpha (12), and TGFbeta (13), is observed. Chronically rejected allografts also have an increase in vascular endothelial growth factor (VEGF), an essential soluble factor which regulates angiogenesis and inflammation and is highly proliferative for vascular cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of proliferating cell nuclear antigen (PCNA) is elevated in grafts with TV (10, 11). Further, increased expression of mitogenic factors, such as PDGF, TGFalpha (12), and TGFbeta (13), is observed. Chronically rejected allografts also have an increase in vascular endothelial growth factor (VEGF), an essential soluble factor which regulates angiogenesis and inflammation and is highly proliferative for vascular cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is known as the major limitation of truly long-term survival. It can develop as early as 3 months after CTx [24], and has become the leading cause of death after the first posttransplant year [20,144,237]. The incidence is angiographically detectable in 30% -50% of recipients by 5 years after CTx [238].…”
Section: Cardiac Allograft Vasculopathymentioning
confidence: 99%
“…The limited involvement of the allograft vasculature with sparing of the recipient's native vessels suggests processes that specifically target the allograft and produce endothelial injury and/or derangement in regulation of the smooth muscle cell growth. Immuno-histochemical studies of allograft vasculopathy demonstrated endothelial expression of the MHC I and II antigens as well as adhesion molecules, such as: vascular cell adhesion molecule (VCAM-1), intercellular adhesion molecule (ICAM-1), and ELAM (E-selectin) which make the vascular endothelium susceptible to be attacked by the immune system via a cellular or humoral mechanism [3,7,27,144,207].…”
Section: Cardiac Allograft Vasculopathymentioning
confidence: 99%
“…Histologically, the vessels of the graft show perivascular fibrosis, smooth muscle cell proliferation accompanied by subendothelial lymphocytes and macrophages [14, 15]. Proliferation is a central feature of transplant vasculopathy lesions and grafts show increased expression of mitogenic factors, such as PDGF, TGFα and TGFβ, and vascular endothelial growth factor, an essential soluble factor which regulates angiogenesis [16-18]. …”
Section: Introductionmentioning
confidence: 99%